2013
DOI: 10.1176/appi.ps.201200394
|View full text |Cite
|
Sign up to set email alerts
|

Disengagement From Care: Perspectives of Individuals With Serious Mental Illness and of Service Providers

Abstract: Individuals with serious mental illness and providers often do not agree on reasons for seeking care. The framework of acceptable, accessible, and available services identifies opportunities for providers to adjust practices and maximize engagement in services among individuals with serious mental illness who are in high need of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 40 publications
1
50
0
1
Order By: Relevance
“…Clinicians reported that Bangladeshi women in the UK [41], and Indian immigrants [45], elderly blacks and Hispanics [44], and Portuguese-speaking immigrants [50] in the United States discontinued medications perceived as unnecessary. However, black, Hispanic, and Asian patients in the US continued medications when clinicians confirmed with family members that the use of medications is a culturally-appropriate expectation of care [58]. The second commonest finding was that clinicians improved treatment continuation after framing communication according to patient interpretations.…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians reported that Bangladeshi women in the UK [41], and Indian immigrants [45], elderly blacks and Hispanics [44], and Portuguese-speaking immigrants [50] in the United States discontinued medications perceived as unnecessary. However, black, Hispanic, and Asian patients in the US continued medications when clinicians confirmed with family members that the use of medications is a culturally-appropriate expectation of care [58]. The second commonest finding was that clinicians improved treatment continuation after framing communication according to patient interpretations.…”
Section: Resultsmentioning
confidence: 99%
“…27 The study included clients identified in the New York City Mental Health Care Monitoring Initiative, a project jointly sponsored by the NYS Office of Mental Health and the NYC Department of Health and Mental Hygiene that operated from 2009-2011 as an effort to improve service coordination for adult NYC residents with serious mental illness. The project involved reviews of Medicaid claims and other state administrative data for high-need populations to identify clients who may not have been receiving needed services, or who used excessive amounts of acute behavioral health services.…”
Section: Methodsmentioning
confidence: 99%
“…28,29 Prior reports have summarized the project's findings regarding numbers of clients disengaged, reasons for disengagement, availability of treatment provider outreach, and re-engagement rates. 27,30,31 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations